Peran Manajemen Hubungan Masyarakat dalam Meningkatkan Citra dan Prestasi di MI Majidul Wathani NW Sekilat - Irwan Yon Hadi; Suparlan Suparlan; Muh. Yurdan Said; Sapinah Sapinah; Tahalli Tahalli (LP2M STIT Palapa Nusantara, 2025)
Although public relations management has become an important part of educational institution management, studies on its role in improving the image and achievements of madrasahs still need to be strengthened through specific institutional contexts. This study aims to describe the role of public relations management in improving the image and achievements of the madrasah, the implementation of public relations strategies, and its supporting and inhibiting factors at MI Majidul Wathani NW Sekilat. This study used a descriptive qualitative approach with a case study design. Data were collected through interviews, observation, and documentation, and were then analyzed qualitatively by strengthening data validity through source, technique, and time triangulation. The results show that public relations plays an important role in building and maintaining a positive image of the madrasah, establishing strategic partnerships, increasing public trust, and supporting the promotion and branding of the madrasah through communication media. However, limitations in organization, infrastructure, and human resources pose challenges in implementing public relations management. The support of the madrasah principal and the participation of teachers and the community are the main supporting factors for the success of public relations management at MI Majidul Wathani NW Sekilat. The conclusion of this study affirms that well-directed public relations management can strengthen institutional image and support the improvement of madrasah achievements. These findings imply the importance of strengthening communication strategies, resource management, and sustainable collaboration between the madrasah and the community.